Lighting level and room temperature audit of a University Campus - Enalyn T. Domingo; Ferdinand L. Marcos; Cid L. Lapuz (Institute of Advanced Engineering and Science, 2023)
An energy audit on a campus was conducted focusing on two parameters: lighting level and temperature. A walk-through survey for each room was done to measure the said parameters. The measurements were then compared with existing standards. It was found out that most of the rooms have lower than the standard average illumination. Meanwhile, there are rooms that have temperatures higher than the recommended values. Proposed improvements include adding lamps and change of T8 to T5 fluorescent bulbs. To address high temperature in the building, simple solutions like door closers and PVC roll curtains are suggested. Further study on the airtightness of the buildings and surface reflectance is recommended.